TAHLĪL AL-AKHTA' FĪ TADRĪB KITĀBAH NUSHUS AL-KHUTBAH - Muhammad Fauzan Saida (Jurnal Al-Maqoyis, 2020)
In this thesis study the author focused discussion on Error Analysis according to Richards et.al in Sunardi (2002:43) stating that error analysis is a theologia of the errors made by the learner of a language as a second language or as a foreign language. The Text of the Khutbah Jum’at Santri of Darul Hijrah Putra who became the object of research, discussion of errors on nahwu, shorof, imla, and meaning in the text of the khutbah jum’at written by last grade students of Darul Hijrah Putra. His goals to describe and analyse the types of errors in training writing the texts are Friday's speech with students at Darul Hijrah Islamic Boarding School Cindai Alus Martapura. And to describe and analyse the factors of common errors in writing texts are Friday's sermon in students at Darul Hijrah Islamic Boarding School Cindai Alus Martapura. And to describe the proposed solutions to address errors among students writing the texts of Friday's speech in students at Darul Hijrah Islamic Boarding School Cindai Alus Martapura. The researcher used this research as a descriptive approach, and the type of research in this research is “office research” and research is the texts of the Friday oration of students at Darul Hijrah Islamic Boarding School Cindai Alus Martapura, and the subject of grammatical, banking, spelling and semantic research. His goals to describe and analyse the types of errors in writing the texts are Friday's speech with students at Darul Hijrah Islamic Boarding School Cindai Alus Martapura. To describe and analyse the factors of common errors in writing texts are Friday's sermon in students at Darul Hijrah Islamic Boarding School Cindai Alus Martapura. To describe the proposed solutions to address errors among students writing the texts of Friday's speech in students at Darul Hijrah Islamic Boarding School Cindai Alus Martapura. The researcher used this research as a descriptive approach, and the type of research in this research is “office research” and research is the texts of the Friday oration of students at the Immigration House Institute, and the subject of grammatical, banking, spelling and semantic research. Factors leading to writing errors mean the lack of students' practice of writing Arabic because of time, poorly the ability of some students in Arab bases.